An Empirical Study of the Small Firm Effect on China Stock Market: Evidence from Shanghai Stock Exchange - GE, Chaorui (2011)
The research of “small firm effect” has attracted numerous academic attentions since Banz (1981) documents this anomaly, it implies either market inefficiency or inadequacies in the underlying asset-pricing model and poses a big challenge to the traditional financial paradigm which asserts rational practitioners. This paper examines the weak form market efficiency on China’s stock market as the premise, and then exploits the small firm effect in a sample of 50 non-financial A-share firms over the period 2005-2010. Empirical results indicate that China’s stock market exhibits weak form efficiency in terms of randomness; the small firms’ superior returns do exist on China’s stock market and are determined by macroeconomic environment (small firm effect is more observable under bear market)and seasonal factor (July turns out to enjoy the largest size premia). Our findings suggest that mean-variance efficient investors in China should seek for undervalued small size firms rather than herding the market fashion. Besides, more efficient supervisory and regulatory revisions should be implemented, to ensure vigorous growth in this emerging market.